Implementation of The “Spy On” Program for English Use in Daily Communication Among Students at Al-Muwahhidin Islamic Boarding School (LITPAM, 2026)
Effective English communication requires consistent use and a supportive environment. However, in Al-Muwahhidin Islamic Boarding School, where English use is implemented, students’ lack of awareness, confidence, and self-honesty in using the language makes the habituation and language acquisition process less optimal. This study aims to explain the implementation of the “Spy On” program as an effort to encourage students to speak English, examine its impact on students’ English use, and identify the challenges faced. This study employed a qualitative instrumental case study. Data were collected through observation (observation checklist and field notes) and semi-structured interviews with 7 participants (4 students, 1 teacher, and 2 administrators). The data were analysed using Miles and Huberman’s model, including data reduction through coding and categorising interview and observation data, data display by presenting reduced data, and conclusion drawing through interpretation and verification of the findings. Technical triangulation was applied to ensure credibility. The results show that the “Spy On” program has the potential to encourage English use by providing comprehensible input through daily interactions, forming language habits through monitoring and practice, and supporting affective adjustment through an adaptation period. Students’ proficiency ranges from the preproduction to intermediate stages, while the challenges identified reflect a natural part of the second-language acquisition process.